Shear strength of landslide clay soil containing weathered serpentinite - Yokota, K.; Yatabe, R.; Yagi, N.; Bhandary, N. P. (Journal of Nepal Geological Society, 2000)
Serpentinite is a rock consisting magnetite, brucite, and serpentine minerals. It is supposed to have formed on the deep sea floor by a sudden eruption of mantle matters or by cracking of the crust and coming in contact with water. It is generally associated with basic and sedimentary rocks. Among three constituent minerals, brucite easily dissolves in water, whereas magnetite does not. Hence, at a border between serpentinite and other rocks, formation of pores in the weathered serpentinite mass takes place due to leaching of brucite. These pores act as groundwater conduits all through the weathered rock mass, causing weathering of other rocks too. In the weathering process, chlorite changes partially to smectite and partially to expansive chlorite, which then form a clay layer with very weak strength. When this clay layer further loses strength, the soil mass resting on it starts moving, creating a landslide. Many landslide sites in Japan lie at the boundary of serpentinite and metamorphic basic rocks like greenschist and black (sedimentary) schist. The slip layer clays of these sites contain various minerals such as serpentine, talc, chlorite, and montmorillonite. The angle of internal friction for serpentinite is about 30°, whereas those of minerals like talc, chlorite, and montmorillonite is between 20° and 10°. In them, the decrease from peak to residual strength is high. Slopes of serpentinite soil containing a high amount of these weak clay minerals are prone to sliding.